MENGINTEGRASIKAN KECERDASAN GANDA DENGAN MODEL PEMBELAJARAN ATRAKTIF BAGI PENDIDIKAN ANAK USIA DINI (PAUD) - Roemintoyo, Roemintoyo (Jurnal Inovasi Pendidikan, 2010)
Multiple intelligence theory is proposed and developed by Howard Gardner. He defined intelligence as a capability in problem resolving and providing a product in varied setting and real situation. This multiple intelligence concept is related to attractive learning. The word ?attractive? has interesting meaning by which besides to attract and provide fun, it also provides creativity and motivates students to play while learning in which this conforms to the main principle of education in kindergarten. There are considerations which must be taken into account by the teacher in implementing attractive learning integrated with multiple intelligence on PAUD (early-aged children education), they are the impact of multiple intelligence on learning method or approach being used class management or setting and the evaluation of learning process. Principally teacher does not only provide lectures but also use problem solving approach adjusted with the student's capability in multiple intelligence theory.